Pemaos In the Sasak Tribe: A Historical Review and Values of Islamic Education - Mutmainnah Mutmainnah; Jamaludin Jamaludin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
The Sasak tribe has various uniqueness and diversity, especially in the case of the traditions that have developed in the Sasak tribe. One of the famous things of the Sasak tribe is about Pemaos as a reading of the lontar script. Specifically, the literal meaning of Pepaosan means reading. The reading of the manuscript in the Pepaosan is carried out by singing or rhythm or by song. This paper specifically has a fundamental question related to Pemaos, because Pemaos has historical roots and has something to do with the Javanese language, this is united in several basic questions, namely, First, what is the meaning of Pemaos in the Sasak tribe. Second, this paper will trace the history of the use and internalization of the values of Islamic education. It is simple that the Pemaos in the Sasak tribe contain important events in their lives, such as births, baby haircuts, circumcision, marriages, and death events. The lontar script that will be read is adjusted to the event that takes place. A Pemaos who reads the Javanese Sasak script lontar, a poet, and two supporters. Their appearance is complemented by offerings placed in a special brass container. Meanwhile, the internalization of the paos in education is that it contains the substance of stories, namely the nature of Pepaosan, which is usually told stories of the journey and life of the Prophets and their companions such as the stories of the Prophet. This forms a character-based education that is able to interact by fostering social behavior among others